A revision of the generic position of Typton australis Bruce, 1973 (Decapoda: Palaemonidae: Pontoniinae), with a new diagnosis for the pontoniine shrimp genus Onycocaridella Bruce, 1981 - Marin, Ivan (Zootaxa, 2008)
Typton australis Bruce, 1973 was described from the Great Barrier Reef, Australia. The species was referred to the genus Typton Costa, 1844 increasing the diversity of the genus in Indo-West Pacific region to six species. At the same time, T. australis shows a developed blade of the scaphocerite and absence of any ornamentation on the orbital and anterolateral margins of the carapace (Bruce 1973, 2000), whereas the type species of the genus Typton, T. spongicola Costa, 1844, possesses well-developed so-called “paraorbital” teeth (Bruce 1972, 1977; I. Marin, pers. observ.). Complete absence of any ornamentation on the orbital and anterolateral margins of the carapace is also known for Typton capricorniae Bruce, 2000 but the blade of the scaphocerite of this species is almost completely reduced as in the other species of the genus Typton.